Guangdong Province: Trade Liberalization and HIV - Lin, Peng (HIV/AIDS in China, 2019)
The Guangdong experience is interesting as a case study, given its role as an economic hub, having attracted both domestic migrant workers, as well as people from abroad ever since the economic reforms of the late 1970s. The first Special Economic Zones were set up in Guangdong, due to its proximity to Hong Kong, most famously in the city of Shenzhen. The region has a prospering manufacturing industry, where both labor-intensive manufacturing products, as well as high-end technology products, are produced and assembled. Trade liberalization and rapid economic growth have also created a booming commercial sex industry and a situation where many economically-marginalized workers are migrating to the region. Here, we document the development of Guangdong’s HIV epidemic, which has grown dramatically from 1997 to 2017, and we describe epidemic response efforts in Guangdong over the same period.